Endogenous prostaglandin E2 potentiates anti‐inflammatory phenotype of macrophage through the CREB‐C/EBP‐β cascade. Issue 9 (20th July 2015) - Na, Yi Rang; Jung, Daun; Yoon, Bo Ruem; Lee, Won Woo; Seok, Seung Hyeok
<x xml:space="preserve">Abstract</x> Macrophages have important functions in tissue homeostasis, but the exact mechanisms regarding wide spectrum of macrophage phenotype remain unresolved. In this study, we report that mouse bone marrow derived naïve macrophages produce prostaglandin E2 (PGE2) endogenously, resulting in anti‐inflammatory gene expression upon differentiation induced by macrophage colony stimulating factor (M‐CSF). Cyclooxygenase (COX) inhibition by indomethacin reduced endogenous PGE2 production of macrophages and subsequently reduced arg1, IL10 and Mrc1, YmI and FizzI gene expressions. Of note, PGE2 phosphorylates CREB via EP2 and EP4 receptor ligation, thereby transcriptionally increasing C/EBP‐β expression in BALB/c bone marrow derived macrophages. Activated CREB directly binds to the CREB‐responsive element of the C/EBP‐β promoter, such that PGE2 ultimately reinforces arg1, IL10 and Mrc1 gene expression. Cyclic AMP activator forskolin also phosphorylated CREB and induced the C/EBP‐β cascade, but this was completely blocked by the PKA inhibitor, H89. Consequently, M‐CSF grown macrophages inhibited T‐cell proliferation but the inhibition ability was reduced when the COX is inhibited by indomethacin or macrophage C/EBP‐β expression was decreased by siRNA transduction. Our results collectively describe the molecular basis for homeostatic macrophage differentiation by endogenous PGE2.